One Size Does Not Fit All: How Leadership Strategies Affect Teacher Satisfaction and Retention. (December 2022) - Baker, Rebecca; Hill, Jenny; Portwood, Brittany; Smith-Harrah, Erin; Hall Sutherland, Daniella
Teacher retention rates continue to plummet at schools across the nation. A principal at Sunnyside Elementary watches firsthand as the revolving door of teachers increases significantly in her brief 3 years of leadership at this school. Once well-known and highly regarded at an award-winning school in the northeast, the principal struggles to delegate, communicate, and acclimate to a high-needs school in the southeastern United States. Yet the practices that worked so well in the northeast sends many of her teachers to search for greener pastures year after year. This case study examines leadership for retention, including communication, organizational climate, and relationship development.